A church after God’s heart : discerning a missional ecclesiology for the Dutch Reformed Church in South Africa - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2019)
Thesis(PhD)--University of Pretoria, 2019.